Kegiatan Dewan Kemakmuran Masjid Dalam Membina Sikap Keagamaan Remaja Di Masjid At-Taqwa Desa Jalaksana Kuningan Jawa Barat - Misna Sutiana; Afring Wasiso (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Today the role and function of the Mosque Prosperity Council (DKM) functions as one of the institutions that fosters and shapes the community to have high religious attitudes and have good morals. The purpose of this study was to determine the activities of the Mosque Prosperity Council in fostering the Religious Attitudes of Youth in At-Taqwa Mosque, Jalaksana Village, Kuningan, West Java. Qualitative research methods with an empirical approach. Collecting data by means of observation, interviews and documentation. The results showed that the activities of the Mosque Prosperity Council in fostering the religious attitude of adolescents at the At-Taqwa Mosque in Jalaksana Kuningan Village, West Java were good, religious activities carried out were: Jurisprudence studies, General Studies, Islamic Date Studies, Yasinan Kultum Subih and social activities.Keywords: Activity; DKM; Attitude; Religious; Youth AbstrakDewasa ini peran dan fungsi Dewan Kemakmuran Masjid (DKM) berfungsi sebagai salah satu lembaga yang membina dan membentuk masyarakat untuk mempunyai sikap keagamaan yang tinggi dan memiliki akhlak yang baik. Tujuan penelitian adalah untuk mengetahui Kegiatan Dewan Kemakmuran Masjid dalam membina Sikap Keagamaan Remaja di Masjid At-Taqwa Desa Jalaksana Kuningan Jawa Barat. Metode Penelitin kualitatif dengan pendekatan empiris. Pengumpulan data dengan cara observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa Kegiatan Dewan Kemakmuran Masjid dalam membina sikap keagamaan remaja Masjid At-Taqwa Desa Jalaksana Kuningan Jawa Barat baik, kegiatan-kegiatan keagamaan yang dilaksanakan yaitu: kajian Fikih, Kajian Umum, Kajian Tarikh Islam, Yasinan Kultum subuh dan kegiatan-kegitan sosial.Kata Kunci: Kegiatan; DKM; Sikap; Keagamaan; Remaja